Modified chlorophyll pigment at ChlD tunes photosystem II beyond the red-light limit - Allgower,F; Sirohiwal,A; Gamiz-Hernandez,AP; Poverlein,MC; Fantuzzi,A; Rutherford,AW; Kaila,VRI (Chemical Science, 2025)
Photosystem II (PSII) is powered by the light-capturing properties of chlorophyll a pigments that define the spectral range of oxygenic photosynthesis. Some photosynthetic cyanobacteria can acclimate to growth in longer wavelength light by replacing five chlorophylls with long wavelength pigments in specific locations, including one in the reaction center (RC) (Science, 2018, 360, 1210–1213). However, the exact location and the nature of these long wavelength pigments still remain uncertain. Here we have addressed the color-tuning mechanism of the far-red light PSII (FRL-PSII) by excited state calculations at both the ab initio correlated (ADC2) and linear-response time-dependent density functional theory (LR-TDDFT) levels in combination with large-scale hybrid quantum/classical (QM/MM) simulations and atomistic molecular dynamics. We show that substitution of a single chlorophyll pigment (ChlD1) at the RC by chlorophyll d leads to a spectral shift beyond the far-red light limit, as a result of the protein electrostatic, polarization and electronic coupling effects that reproduce key structural and spectroscopic observations. Pigment substitution at the ChlD1 site further results in a low site energy within the RC that could function as a sink for the excitation energy and initiate the primary charge separation reaction, driving the water oxidation. Our findings provide a basis for understanding color-tuning mechanisms and bioenergetic principles of oxygenic photosynthesis at the far-red light limit.